2015
DOI: 10.2147/ov.s87369
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an oncolytic adenovirus vector constructed to target the cMet receptor

Abstract: The cMet receptor is a homodimer with tyrosine kinase activity. Upon stimulation with its ligand, hepatocyte growth factor (HGF), the receptor mediates wide physiologic actions. The HGF-cMet signaling pathway is dysregulated in many cancers, which makes cMet an important target for novel therapeutic interventions. Oncolytic adenoviruses (Ads) have been used for the past three decades as a promising therapeutic approach for a wide array of neoplastic diseases. To date, achieving cancer-specific replication of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…We previously utilized the T4 fibritin platform to successfully retarget an oncolytic adenovirus to the cMet receptor in hepatocellular carcinoma and breast cancer [48]. Ad5 binding is mediated by the CXADR receptor, and entry is facilitated in a two-step uptake mechanism by the αvβ3 and αvβ5 integrins as well as other integrins that recognize Arg-Gly-Asp (RGD) motif that is expressed on the penton base protein [49].…”
Section: Discussionmentioning
confidence: 99%
“…We previously utilized the T4 fibritin platform to successfully retarget an oncolytic adenovirus to the cMet receptor in hepatocellular carcinoma and breast cancer [48]. Ad5 binding is mediated by the CXADR receptor, and entry is facilitated in a two-step uptake mechanism by the αvβ3 and αvβ5 integrins as well as other integrins that recognize Arg-Gly-Asp (RGD) motif that is expressed on the penton base protein [49].…”
Section: Discussionmentioning
confidence: 99%
“…For example, AdLuc(HRG-fiber) containing the Heregulin (HRG) ligand in the HI loop of the Ad knob domain successfully retargeted the virus to the receptor tyrosine-protein kinase erbB-3 (HER3) in breast cancer cells [ 22 ]. Another oAd, Ad5-pIX-RFP-FF/NK2, retargeted the oAd to the tyrosine kinase receptor Met (cMet), which was found to be overexpressed in a variety of cancers, including breast cancer [ 23 , 24 ]. In addition, chimeric Ads using alternative serotypes, such as the…”
Section: Group I Virusesmentioning
confidence: 99%
“… 14 MET activation induces multiple signaling cascades associated with cell proliferation, migration, invasion, survival, and branching morphogenesis. 15 , 16 , 17 Dysregulation of the HGF/MET signaling axis has been described in a variety of malignant and premalignant lesions, including lung cancer, gastroesophageal cancer, hepatocellular carcinoma, breast cancer, ovarian cancer, multiple myeloma, and colorectal cancer 18 , 19 , 20 , 21 , 22 , 23 , 24 and is associated with tumor growth, angiogenesis, invasion, and metastasis. 25 , 26 MET gene amplification has been reported in approximately 8% of patients with gastric cancer by fluorescence in situ hybridization (FISH) analysis, 8 , 27 , 28 , 29 while polymerase chain reaction (PCR)‐based assays showed that the occurrence of MET gene copy number increases to approximately 20%.…”
Section: Introductionmentioning
confidence: 99%